Coordinated optimization and management of oxygen content and cathode pressure for PEMFC based on hybrid nonlinear robust control - Fang Shiyi; Feng Jianan; Zhu Yuxin; Chen Zehang; Fang Xiening; Chen Daifen; Fan Xinyu (Science and Technology for Energy Transition)
Cathode inlet and exhaust management remains a significant challenge in Proton Exchange Fuel Cell (PEMFC). Achieving optimal oxygen content in real-time through precise control of the inlet gas is crucial for maintaining optimal output. Additionally, coordinating the air inlet and exhaust to ensure consistent cathode and anode pressures is essential for balancing the internal stack pressure and preventing nitrogen penetration, thereby enhancing PEMFC’s stability and lifespan. In this paper, a hybrid control strategy based on a fifth-order nonlinear mathematical model of the PEMFC cathode is proposed to address these challenges. The strategy combines two Non-singular Fast Terminal Sliding Mode Controllers (NFTSMC) to optimize the oxygen content and pressure control under dynamic load conditions. The NFTSMC avoids the potential singularity problem of terminal sliding mode control by optimizing sliding mode surfaces, while ensuring convergence in finite time. The results demonstrate the effectiveness of the proposed control method in coping with external disturbances and load variations faced by the PEMFC system, as well as dealing with the uncertainty of the PEMFC.